THE STUDY OF LEARNING STRATEGIES USED BY INDONESIAN EFL LEARNERS IN LEARNING ENGLISH GRAMMAR - zafira Ramdayani SA. Kadir; Alfan Zuhairi; Eko Suhartoyo (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
Abstract: The study aimed to investigate the grammar learning strategies frequently used by Indonesian EFL learners in general and grammar learning strategies frequently used by successful and less successful students in learning grammar. The research design of this study is a quantitative study in the form of comparative design. There were 70 students of the second years of English education department participate in this study, and they divided into successful and less successful categories by using the TOEFL structure test consisting of 15 multiple choices and 25 error analysis. Besides, 70 items of the GLSI questionnaire used to know the grammar learning strategies used by the students. The result of the study showed that EFL students used social strategies more frequently than the other strategies. Moreover, both successful and less successful students used the same grammar learning strategies while they were different in frequency use levels. It was also proved that there is no significant difference between successful and less successful EFL students in using grammar learning strategies.Keywords: Learning Strategies, grammar, achievement